Apophytes as invasive plants in the vegetation of Poland - Zając, Maria; Zając, Adam (Biodiversity: Research and Conservation, 2010)
Apophytes are native synanthropic plants, i.e. those found in disturbed habitats. Some apophytes with a limited geographic range, which are native to one part of a country, migrate out of their natural communities as "invasive" plants. We selected from the group of apophytes in Poland (more than 220 species) examples of such plants, which after World War II colonized new areas and often new habitats. They include, for instance, coastal species of dunes and salt marshes, or plants used as ornamentals. Moreover, some species of fresh meadows in the south of Poland, are now found in the north in ruderal habitats. The speed of colonization is high, such that in the last 20 years, starting from a few locations, some have taken over almost the entire area of Poland. The expansion of apophytes can be much faster than that of anthropophytes because apophytes have a higher number of diaspores or a shorter period of adaptation in new localities.